2018
DOI: 10.1002/eap.1780
|View full text |Cite
|
Sign up to set email alerts
|

Different responses of predator and prey functional diversity to fragmentation

Abstract: The study of functional diversity, or the range of species' ecological roles in a community, is a rapidly expanding area in ecology. Given the extent that ecosystems are being altered, effort should shift toward assessing variation in functional diversity across landscapes with the goal of improving land use management decisions. We construct a workflow that creates three-dimensional surfaces and maps of functional diversity to examine changes in beetle functional diversity across an Indiana, USA landscape. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 69 publications
(111 reference statements)
0
10
0
Order By: Relevance
“…3d). To go deeper into ecological questions, it would be advisable to add analysis of functional diversity of prey, such as prey diversity indices, to receive a better understanding of how the ecosystem works [57][58][59] . By achieving this, we will reach a novel insight into the ecology of insectivores, how predators are linked through shared prey, and to which extent the declining populations of both might alter these interactions.…”
Section: Discussionmentioning
confidence: 99%
“…3d). To go deeper into ecological questions, it would be advisable to add analysis of functional diversity of prey, such as prey diversity indices, to receive a better understanding of how the ecosystem works [57][58][59] . By achieving this, we will reach a novel insight into the ecology of insectivores, how predators are linked through shared prey, and to which extent the declining populations of both might alter these interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Anthropogenic disturbances create drier and warmer environments (Gallo and Owen 1999;Kalnay and Cai 2003;Yang et al 2017), and species sensitive to those changes (e.g., lichens and mosses) are known to develop markedly different communities in urban versus non-urban areas (Lättman et al 2014;Oishi 2018). Recent studies have demonstrated that land-use changes have a large influence on functional diversity, which is closely related to ecosystem services (Kissick et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although there has been increased interest in biodiversity-urbanization relationships in recent years, the available literature is biased towards vertebrate studies, especially birds (Ritchie and Johnson 2009;Gagné and Fahrig 2011). Yet invertebrates represent a majority of animal diversity (Groombridge and Jenkins 2002) and have distinctive ecological functions (Mason 1970;Kissick et al 2018). Moreover, molluscs are important conservation targets because of their high diversity, large number of extinction records (Lydeard et al 2004), and ability to be used as ecosystem indicators due to their limited dispersal ability (Hodges and McKinney 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that changes to available resources arising from fragmented habitats negatively impact prey species more than predator species (Kissick et al. ). Herein, we investigate restorative management strategies and custom tools that may be used to curtail or reverse undesirable shifts experienced by wildlife populations in anthropogenically altered habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Human subsidies may change habitat conditions such that once rare resources, such as food, water, and nesting opportunities, are increasingly available for nuisance wildlife use. Recent evidence suggests that changes to available resources arising from fragmented habitats negatively impact prey species more than predator species (Kissick et al 2018). Herein, we investigate restorative management strategies and custom tools that may be used to curtail or reverse undesirable shifts experienced by wildlife populations in anthropogenically altered habitats.…”
Section: Introductionmentioning
confidence: 99%